Research on haematological and biochemical parameters of Bac Ha and H'Mong dog blood - Thu, Do Van; Bo, Nguyen Bach; Binh, Doan Viet; Hung, Nguyen Ngoc; Khoi, Tran Xuan; Hue, Le Thi; Thinh, Nguyen Thi (Academia Journal of Biology, 2015)
Bac Ha and H’mong dog are two endemic species in Lao Cai province. They have many good characteristics to be able to train a working dog. So we have studied the physiological indicators of their blood biochemical basis for service of using them later. One hundred twenty blood samples from 30 dogs (15 dogs Bac Ha, 15 dogs H'Mong). Dogs are aged between 12 and 27 months. Using Neubauer hemocytometer and Shali Haemometer to determine the number of erythrocytes and leukocytes and levels of hemoglobin. Determination of enzyme activity GOT by IFCC method without pyridoxalphosphat. GPT was determined by the method DGKC on automated analyzers Autohumalyzer F1. Bac Ha dog RBC was 7.8166 million/mm3, WBC was 10.993 thousand/mm3, hemoglobin level was 16.347 g%. Dogs Hmong RBC was 7.8219 million/mm3, WBC was 11.511 thousand/mm3, hemoglobin concentration was 16.052 g%. Bac Ha dog GOT activity was 62.51 U/L, GPT activity was 34.66 U/L. Hmong dog GOT enzyme activity was 57.35 U/L, GPT enzyme activity is 33.54 U/L.